A Soft/Hard Magnetic Nanostructure Based on Multisegmented Coni Nanowires - Escrig-Murua, J; Palma-Solorza, J; Pereira-Abarca, A; Casagrande-Denardin, J (ROYAL SOC CHEMISTRY, 2015)
In this paper we have introduced a new soft/hard nanostructure based on multisegmented CoNi nanowire arrays having diameters of around 110 nm and made of five segments with nominal compositions of Co, Co66Ni33, Co50Ni50, Co33Ni66 and Ni, each of which has a length of 800 nm, so that the total length of the multisegmented nanowire is 4 mm. These arrays have been synthesized by means of potentiostatic electrodeposition into the pores of hard-anodic alumina templates. The morphology, chemical composition and microstructure of the multisegmented CoNi nanowires were determined by high-resolution scanning electron microscopy, energy dispersive X-ray microanalysis, and powder X-ray diffraction method, respectively. The room temperature magnetic behavior of the multisegmented nanowire arrays is also studied and compared with CoNi nanowire arrays with homogeneous composition (non-segmented nanowires), synthesized in the same templates and having the same dimensions as the segmented ones. These nanostructures could be used to control the movement of magnetic domain walls. In this way, these nanostructures can be an alternative to store information or even perform logic functions.